Pemberdayaan Masyarakat Sadar Teknologi, Bahasa dan Anti Narkoba di Masyarakat Kampung Panglong - Hedensy, Hedensy; Fani, Fani; Hendy, Hendy; Wanandi, Sofyan; Fany, Fany; Astuti, Eria; Hudori, Mahfuz (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
The purpose of holding this program is the understanding of adolescents about the dangers of drugs, the importance of limiting and monitoring the use of technology from parents to children, the importance of English in this globalization era, and increasing children?s knowledge of English. The method of this program was carried out in the Panglong village RT 04 RW 11 ( socialization, material, and understanding provided ). The result of this program is that local residents are more aware of the dangers of drugs, increased knowledge of English and insight on understanding the use of technology.